РАЗВИТИЕ КРЕАТИВНЫХ ИНДУСТРИЙ КАК ПРИОРИТЕТ МОДЕРНИЗАЦИИ КАЗАХСТАНА - G. T. Shilimbetova (Экономика: стратегия и практика)
The article is devoted to the assessment of the potential of Kazakhstan’s creative industries as a priority of Kazakhstan’s modernization. To achieve this goal, the methods of statistical, inductive and deductive analysis were used. The analysis was based on the model of concentric circles of David Throsby. To achieve the goal set before this article, the world market of creative industries was first considered, further development of these industries in Kazakhstan was analyzed, and programs to support the creative and cultural industries of Kazakhstan were considered.During the analysis, it was revealed that the development of creative industries in Kazakhstan is stable and positive.